Teachers’ Perception on E-Learning at Vocational High School - Nina Agustina; Dila Charisma; Hanif Nurcholish Adiantika (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2021)
The covid-19 pandemic has brought significant changes in every aspect of human life, including education. Indonesian Education and Culture Minister, Mr. Nadiem Anwar Makarim ordered all students including university students to research from home. Thus, the use of e-learning is the best choice in order that teaching and learning process run as well. This research aimed at knowing the teachers’ perception on e-learning at Vocational High School. The data was collected through interview. The participants were 3 English teachers selected by non-probability sampling which purposive sampling technique. The researcher used descriptive qualitative as a design method because it was considered as an appropriate approach as a type of research. The result of this research was presented descriptively in order to reveal the teachers' perception towards e-learning comprehensively. The research found that mostly the teachers gave good perception about e-learning. They improved their teaching through e-learning and got a new experience of the new media applied in teaching activity. Whereas, some teachers also gave perception that e-learning has obstacles that bad network, and the capacity of the application used in e-learning. Keywords: Teachers’ perception; E-learning